Parkinson's disease sleep scale-validation of the revised version PDSS-2 - Trenkwalder, Claudia; Kohnen, Ralf; Högl, Birgit; Metta, Vinod; Sixel-Döring, Friederike; Frauscher, Birgit; Hülsmann, Julia; Martinez-Martin, Pablo; Chaudhuri, Kallol Ray (Movement disorders, 2011)
Background: The previous Parkinson's disease sleep scale (PDSS) is a 15‐item visual analogue scale that assesses the profile of nocturnal disturbances in Parkinson's disease (PD) patients. Objective: To extend the scale so that it becomes a frequency measure scale with five categories and encompasses unmet needs such as restless legs syndrome, akinesia, pain, and sleep apnea. Methods: For validation of the PDSS‐2, PD patients' ratings and investigators' interviews were compared to ratings from a semistructured interview with a caregiver/partner, and to related scales. PDSS‐2 was repeated for test‐retest‐reliability after 1–3 days. Results: A total of 113 PD patients showed a mean (SD) total score of 16.5 (±8.9) (range: 2–40) indicating mild to moderate sleep disturbances. PDSS‐2 item‐total correlation for proving internal consistency was satisfactory (correlations >0.30). From a factor analysis, three subscales were derived: (1) “motor problems at night,” (2) “PD symptoms at night” and (3) “disturbed sleep.” The alpha coefficient for the total score was 0.73, for subscales 0.47 to 0.66. The test‐retest‐reliability intra‐class‐coefficient for the total score was 0.80, with 0.69 and 0.77 within the subscales. For discriminative validity, significant differences were found in the PDSS‐2 total score depending on CGI and Hoehn and Yahr severity levels. A comparison between caregivers' and patients' ratings was carried out. Conclusion: The PDSS‐2, with an extended spectrum of nocturnal disabilities and easier use for patients, is a reliable, valid, precise, and potentially treatment‐responsive tool for measuring sleep disorders in PD. © 2011 Movement Disorder Society